Africa's Path to Net-Zero Exploring Scenarios for a Sustainable Energy Transition - Nwokolo, Samuel Chukwujindu; Singh, Rubee; Khan, Shahbaz; Kumar, Anil.; Luthra, Sunil (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book provides a comprehensive analysis of the challenges and opportunities for achieving a net-zero energy transition in Africa. With a focus on policy, technology, financing, and socio-political factors, the book presents four potential scenarios for a sustainable energy transition in the continent. The scenarios presented highlight the importance of balancing economic growth with environmental sustainability and social development. While foreign investments in renewable energy could be beneficial, they must be carefully monitored and regulated to prevent exploitation and ensure accountability. The book also emphasizes the need for collaboration and a calculated transition to ensure that all stakeholders are involved in the process. Additionally, the challenges of achieving self-sufficiency and export-free energy are discussed, with the importance of setting limitations and regulations to prevent a vicious cycle of poverty and dependency on foreign aid. With a deep understanding of Africa's environmental, socio-political, and socio-cultural complexities, "Africa's Path to Net-Zero" offers valuable insights for policymakers, investors, and anyone interested in promoting a sustainable energy future for the continent.
1. Introduction - Africa's Net Zero Transition -- 2. Global Investment and Development in Africa -- 3. Remedies to the Challenges of Renewable Energy Deployment in Africa -- 4. Influencing The Scale of Africa's Energy Transition -- 5. Technological Pathways to Net-Zero Goals in Africa -- 6. Decarbonizing Hard-to-Abate Sectors in Africa -- 7. Impacts of Climate Change in Africa -- 8. Scenarios that Could Give Rise to an African Net-Zero Energy Transition -- 9. Africa's Awakening to Climate Action.
Keywords: Africa -- Economic conditions; Sustainability; Power resources; Economics; African Economics; Sustainability; Natural Resource and Energy Economics; Political Economy of Energy